Effects of Plant Growth-Promoting Bacteria (PGPB) Inoculation on the Growth, Antioxidant Activity, Cu Uptake, and Bacterial Community Structure of Rape (Brassica napus L.) Grown in Cu-Contaminated Agricultural Soil - Ren, Xue-Min; Guo, Shi-Jun; Tian, Wei; Chen, Yan; Han, Hui; Chen, E.; Li, Bai-Lian; Li, Yu-Ying; Chen, Zhao-Jin (Frontiers in Microbiology, 2019)
Previous analyses of plant growth-promoting bacteria (PGPB) combined with the remediation of heavy metal pollution in soil has largely been performed under potting or greenhouse conditions, and in situ remediation experiments under field conditions have rarely been reported. In this study, the effects of the metal-resistant PGPB Microbacterium oxydans JYC17, Pseudomonas thivervalensis Y1-3-9, and Burkholderia cepacia J62 on soil Cu pollution under rape remediation were studied in the farmland surrounding the Nanjing Jiuhuashan copper mining region in China. Following inoculation treatment for 50 days, the biomasses of the rape inoculated with strains JYC17, Y1-3-9, and J62 increased, and the total amounts of Cu uptake increased by 113.38%, 66.26%, and 67.91%, respectively, thus improving the Cu remediation efficiency of the rape. Y1-3-9 and J62 affected the bioavailability of Cu in the soil, and the water-soluble Cu contents were increased by 10.13% and 41.77%, respectively, compared with the control. The antioxidant activities in the rape leaves showed that the tested bacteria increased the contents of antioxidant nonenzymatic substances, including ascorbic acid (ASA) and glutathione (GSH), which were increased by 40.24%-91.22% and 9.89%-17.67%, respectively, thereby reducing the oxidative stress caused by heavy metals and the contents of thiobarbituric acid-reactive substances (TBARS) and peroxidase (POD). PCR-denaturing gradient gel electrophoresis (PCR-DGGE) was used to analyze the effects of the tested bacteria on the cultivation-dependent and cultivation-independent bacterial communities in the root endosphere and rhizosphere soil of the rape. The sequencing results of the DGGE bands indicated that the tested bacteria colonized the endosphere and rhizosphere, and they became an important component of the cultivation-dependent bacteria. The canonical correspondence analysis (CCA) of the DGGE profile and similarity cluster analysis showed that the tested bacteria affected the cultivation-dependent and cultivation-independent bacterial communities in the root endosphere and rhizosphere. In this experiment, the effects and mechanisms of the combined plant-microbe remediation under field conditions were preliminarily studied, and the results are expected to provide a theoretical basis for future combined remediation experiments.